Improving the Efficiency and Effectiveness Principles in Making Laws: Challenges and Opportunities - Fadli, Muhammad; Ruslan, Achmad; Ilyas, Anshori; Pangerang Moenta, Andi (International Journal of Psychosocial Rehabilitation, 2020)
As a constitutional state, the administration of government in Indonesia is based on statutory regulations. The process of establishing laws in Indonesia requires a gradual process and takes a long time. Starting from the stages of planning, drafting, discussion, ratification, until the enactment stage. Hence, one of the most essential stages in the formation of legislation in the planning stage through the National Legislation Program. This paper is a normative legal research with using statute, conceptual, and comparison approaches. The results show that the comparison of the number of bills in the national legislation program with the number of bills successfully enacted is vastly different. However, as it turns out into practice, this phenomenon occurs almost every year without any efforts to improve the legislation system. The number of bills in the National Legislation Program 2010-2014 totaled 258 bills, while only 83 bills were successfully completed, or only 16 percent according to the National Legislation Program. Indeed, Indonesia should apply the principles of efficiency and effectiveness consequently as basic principles in making laws.